Immobilization and Characterization of Enzyme-Functionalized Gold Nanoparticles on Gold Surfaces through Streptavidin-Biotin Binding - Handali, Paul R (Langmuir : the ACS journal of surfaces and colloids, 2025)
A critical step to developing enzyme-based technologies such as biosensors and biofuel cells is immobilizing the enzyme of interest onto an abiological substrate. Currently, there is a lack of generalizable strategies to immobilize enzymes onto different surface substrates, requiring the development of new chemical functionalization for each surface-enzyme pair. Gold nanoparticles (AuNP) have been shown to be effective scaffolds for bound enzymes that retain activity and, importantly, have longer-term stability than their native aqueous solution counterparts. In this work, we demonstrate a significant step toward a generalizable surface immobilization method for enzymes, where we conjugated horseradish peroxidase functionalized gold nanoparticles (AuNP-HRP) onto thiol-functionalized solid gold surfaces (SGS) using biotin-streptavidin interactions. We determined that ∼ 0.2 pmol of AuNP-HRP is bound to the SGS and that it retains 2% of its activity compared to the AuNP-HRP conjugate in solution. While we observe a significant reduction in activity of the enzyme, this system can be significantly optimized to improve activity. Importantly, we demonstrate that immobilization on AuNP can be used as an intermediate material to bind enzymes on surfaces independent of the chemistry governing the formation of the AuNP-enzyme conjugate. We discuss how this strategy can be expanded to other types of surfaces such as semiconductors and plastics